Effect of particle size and composition on local magnetic hyperthermia of chitosan-Mg1−xCoxFe2O4 nanohybrid - Islam, M. Aminul; Syed, Ishtiaque M.; Mamun, M. Al; Hoque, S. Manjura (Frontiers in Chemistry, 2024)
In this study, Mg1−xCoxFe2O4 (0≤x ≤ 1 with ∆x = 0.1) or MCFO nanoparticles were synthesized using a chemical co-precipitation method and annealed at 200, 400, 600, and 800°C respectively to investigate the structural properties of the materials by X-ray diffractometer (XRD), transmission electron microscopy (TEM), and Fourier-transform infrared spectroscopy (FTIR). Controlled annealing increased particle size for each value of x. The aim was to investigate how specific loss power (SLP) and maximum temperature (Tmax) during local magnetic hyperthermia were affected by structural alterations associated with particle size and composition. The lattice parameter, X-ray density, ionic radius, hopping length, bond length, cation-cation distance, and cation-anion distance increase with an increase in Co2+ content. Raman and FTIR spectroscopy reveal changes in cation distribution with Co2+ content and particle size. Magnetic properties measured by the physical property measurement system (PPMS) showed saturation magnetization (Ms), coercivity (Hc), remanent magnetization (Mr/Ms), and anisotropy constant (K1) of the Mg1−xCoxFe2O4 nanoparticles increase with Co2+ content and particle size. When exposed to an rf magnetic field, the nanohybrids experienced an increase in both the SLP (specific loss power) and Tmax (maximum temperature) as the particle size initially increased. However, these values reached their peak at critical particle size and subsequently decreased. This occurs since a modest increase in anisotropy, resulting from the presence of Co2+ and larger particle size, facilitates Néel and Brownian relaxation. However, for high anisotropy values and particle size, the Néel and Brownian relaxations are hindered, leading to the emergence of a critical size. The critical size increases as the Co2+ content decreases, but it decreases as the Co2+ content increases, a consequence of higher anisotropy with the increase in Co2+. Additionally, it is noteworthy that the maximum temperature (Tmax) rises as the concentration of nanohybrids grows, but the specific loss power (SLP) decreases. An increased concentration of chitosan-MCFO nanohybrids inhibits both the Néel and Brownian relaxation processes, reducing specific loss power.